Full-Cycle Micro-Organizational Behavior Research - Chatman, Jennifer A.; Flynn, Francis J. (Organization Science, 2005)
We advocate a full-cycle approach to conducting organizational behavior research. Full-cycle research begins with the observation of naturally occurring phenomena and proceeds by traveling back and forth between observation and manipulation-based research settings, establishing the power, generality, and conceptual underpinnings of the phenomenon along the way. Compared with more traditional approaches, full-cycle research offers several advantages, such as specifying theoretical models, considering actual and ideal conditions, and promoting interdisciplinary integration. To illustrate these advantages, we provide examples of an implicit approach to conducting full-cycle research and present suggestions for fostering more explicit full-cycle research programs in the future. We encourage individual researchers to adopt this approach rather than to assume the field will naturally avoid the inevitable vulnerabilities that emerge from relying on particular methodological approaches. We conclude by discussing the relevant constraints and opportunities for engaging in full-cycle organizational research.